The research output of academic economists in Brazil (Economia Aplicada, 2000)
This paper presents productivity rankings of economics departments and economists in Brazil. The results are: 1) At individual level, only 9 out of 506 economists managed to publish at least one paper in the top journals of economics, and 52 economists published at least one paper in a wide list of internationaljournals; 2) The areas in which Brazilian research is most internationally successful are: Development economics, mathematical economics, and post Keynesian economics; 3) There is a remarkable difference in academic quality among the departments; 4) The performance of departments strongly depends on the individual excellence of a very small number of people. These findings suggest that academic productivity in Brazil is poor when evaluated by international criteria. As a policy prescription it is recommended that economics departments in Brazil should establish international publications as a target for their members, and governmental agencies of research should cut the grants of unproductive departments and scholars.